Design and synthesis of novel P2Y2 receptor ligands - Conroy, S. (2018)
The P2Y2 receptor (P2Y2R) has been implicated in a range of clinical conditions, including but not limited to: cystic fibrosis, dry eye syndrome and cancer. However, a lack of high quality, drug-like modulators and tool-like compounds means there is scope to develop ligands that can further probe P2Y2R function in vitro and in vivo.